Kritik Wacana atas Transformasi Maqāṣid al-Syarī’ah dalam Studi Islam Kontemporer - Sugitanata, Arif (Program Studi Hukum Ekonomi Syariah, 2025)
The resurgence of Maqāṣid al-Sharī’ah discourse in contemporary Islamic studies is often positioned as a flexible bridge between divine values and the aspirations of modernity. It is hailed as an ethical framework capable of harmonizing Islamic legal tradition with the principles of social justice, human rights, and democracy. However, behind this euphoria lies a critical issue concerning how Maqāṣid is produced, claimed, and disseminated as a discourse imbued with various interests. This study aims to deconstruct the discourse of Maqāṣid in recent Islamic scholarship by tracing its shift from a normative analytical tool to an ideological instrument that often blurs the line between interpretation and political legitimization. This research was conducted through a literature study employing a descriptive-analytical-exploratory qualitative approach, utilizing Norman Fairclough’s Critical Discourse Analysis (CDA) as the analytical framework. The findings reveal that Maqāṣid is utilized not only to interpret Islamic law but also to reframe social reality through normative narratives that appear universal yet carry specific ideological underpinnings. In academic practice, it has evolved into an epistemic commodity that affirms liberal agendas without necessarily adhering to the rigorous methodologies of Islamic scholarship. In the political sphere, it functions as a rhetorical ornament of the nation-state to gain ethical legitimacy for policies that may not reflect the substantive values of Sharī’ah. Through the lens of CDA, this study positions Maqāṣid not merely as an interpretive tool but as a discursive practice that reflects power relations in the production of contemporary Islamic knowledge. Thus, this research offers not only a critique of the Maqāṣid euphoria but also calls for the restoration of a more reflective, open, and historically conscious discursive space in the development of an honest and resilient Islamic epistemology.